Inventory of medium and large mammals in the Biological Reserve of Araucárias, Paraná, Brazil - D'Bastiani et al., Elvira (Acta Biológica Paranaense, 2018)
<htm>Inventory of medium and large mammals in the Biological Reserve of Araucárias, Paraná, Brazil</htm>